2012
DOI: 10.1177/1470320312459976
|View full text |Cite
|
Sign up to set email alerts
|

ACE I/D and eNOS E298D gene polymorphisms in Saudi subjects with hypertension

Abstract: There is increased frequency of ACE and eNOS mutant allele carriage among Saudi patients affected with hypertension, particularly if accompanied by obesity and diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 48 publications
1
27
1
Order By: Relevance
“…Also the recessive model (DD versus II+ID) showed an association with hypertension with an adjusted odds ratio of II+ID 1.79(95% CI: 1.09-2.92) (data not shown in Table 4), indicating that the ACE gene I/D polymorphism appeared strong evidence to support the role of the D-allele and/or DD genotype as a risk factor for hypertension. These findings are in agreement with those of Ahmad Ali [2], who noted that hypertensive cases showed a significantly higher frequency of the ACE mutant D allele carriage than I allele carriage. Also, Zarouk et al [1] reported that DD genotype and the D allele are significantly associated with hypertension in Egyptian patients, A significant association between the I/D variant and hypertension was also found among Han Chinese through recent meta-analysis [3].…”
Section: Discussionsupporting
confidence: 93%
“…Also the recessive model (DD versus II+ID) showed an association with hypertension with an adjusted odds ratio of II+ID 1.79(95% CI: 1.09-2.92) (data not shown in Table 4), indicating that the ACE gene I/D polymorphism appeared strong evidence to support the role of the D-allele and/or DD genotype as a risk factor for hypertension. These findings are in agreement with those of Ahmad Ali [2], who noted that hypertensive cases showed a significantly higher frequency of the ACE mutant D allele carriage than I allele carriage. Also, Zarouk et al [1] reported that DD genotype and the D allele are significantly associated with hypertension in Egyptian patients, A significant association between the I/D variant and hypertension was also found among Han Chinese through recent meta-analysis [3].…”
Section: Discussionsupporting
confidence: 93%
“…A study of a Saudi population noted a higher frequency of the mutant deletion allele in hypertensive cases with a BMI of ≥30 kg/m 2 in comparison to controls, although the difference was not significant. 20 However, this result was reversed in the current study, as the frequency of the deletion allele among the hypertensive overweight/obese group was significantly lower than the control group. A similar study performed on Korean women also confirmed this finding (P = 0.063).…”
Section: Discussioncontrasting
confidence: 46%
“…Study conducted by He et al on Chinese population suggested that the ACE D allele was significantly associated with hypertension (31). Also, Ahmad Ali's study confirmed these results and noted that hypertensive cases have significantly higher frequency of the ACE mutant D allele carriers than I allele carriers (32). In association to the elite sport performance, it is well known that RAAS plays an important role in the regulation of myocardial growth, by increasing of plasma Ang II concentrations, leading to left ventricular hypertrophy (33).…”
Section: The Frequency Of Ace I/d Polymorphism In General Population mentioning
confidence: 72%